Identifying Risk Factors Affecting the Usage of Digital and Social Media: A Preliminary Qualitative Study in the Dental Profession and Dental Education - Rayan Sharka; Jonathan P. San Diego; Melanie Nasseripour; Avijit Banerjee (MDPI AG, 2021)
Aims: This study aimed to identify the risk factors of using DSM to provide an insight into the inherent implications this has on dental professionals in practice and trainee professionals' education. Materials and methods: Twenty-one participants (10 dental professionals and 11 undergraduate and postgraduate dental students) participated in this qualitative study using semi-structured interviews in a dental school in the UK. The interviews were analysed and categorised into themes, some of which were identified from previous literature (e.g., privacy and psychological risks) and others emerged from the data (e.g., deceptive and misleading information). Results: The thematic analysis of interview transcripts identified nine perceived risk themes. Three themes were associated with the use of DSM in the general context, and six themes were related to the use of DSM in professional and education context. Conclusions: This study provided evidence to understand the risk factors of using DSM in dental education and the profession, but the magnitude of these risks on the uptake and usefulness of DSM needs to be assessed.